The Effects of Mindfulness on Persons with Mild Cognitive Impairment: Protocol for a Mixed-Methods Longitudinal Study - Wong, Wee Ping; Hassed, Craig; Chambers, Richard; Coles, Jan (Frontiers in Aging Neuroscience, 2016)
Introduction Mild cognitive impairment (MCI) not only negatively impacts upon a person's life, but it is also seen as an intermediate stage on the progression to Alzheimer's Disease (AD), and therefore warrants early intervention. However, there is currently no effective pharmacological treatment approved for MCI. There is a paucity of evidence that non-pharmacological interventions such as cognitive training could result in improvements in the daily activities functioning of persons with MCI. Growing evidence has shown that mindfulness meditation increases gray matter volume and concentration in brain regions such as the hippocampus and prefrontal cortex, strengthens brain functional connectivity, and enhances psychological well-being which could be beneficial to counteract the memory and cognitive decline of MCI. Aims We aim to quantitatively investigate whether mindfulness practice can improve the cognitive function, psychological health, mindfulness and functional abilities in activities of daily living of the MCI participants over time; the relationship between the amount of mindfulness practice and degree of improvement in these health outcomes; and the differential effects and interactions of both formal and informal mindfulness practices. We will also qualitatively address the issues about the MCI participants’ and familiar support persons’ engagement with the program, the nature of group interactions, their program experience, their perceived effects and expectations of mindfulness practice, and the challenges encountered in practising mindfulness. Methods Our study is one of the first mixed-methods longitudinal studies with a one-year follow-up using a pre- and post-intervention design. It involves the MCI participants and their familiar support person in a customised 8-week group-based mindfulness training program. The outcome measures will use the Montreal Cognitive Assessment, Depression Anxiety Stress Scale, Freiburg Mindfulness Inventory and Bayer Activities of Daily Living Scale. The qualitative methods will include participant observation during the program and semi-structured interviews at post-intervention and one-year follow-up. Significance This customized MCI group mindfulness training program presents as a promising and feasible non-pharmacological therapeutic intervention option for MCI and a possible preventive strategy for Alzheimer’s disease. This study has been registered in the Australian New Zealand Clinical Trials Registry (ANZCTR) (URL: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=366695) and allocated the ACTRN: ACTRN12614000820606.